Purchasing Decisions for Cosmetic Products Through Retail Cosmetic Stores: Analysis of Retail Marketing Mix and Halal Awareness - Nadzira Azzahra; Hilda Monoarfa; Rumaisah Azizah Al Adawiyah (LAA MAISYIR : Jurnal Ekonomi Islam, 2024)
The purpose of this study is to provide an overview and analyze the following factors: price, location, product diversity, and store atmosphere in the retail mix and halal awareness on customer decisions to buy halal cosmetics products at Sociolla stores in Bandung. This research uses a descriptive causality approach and uses SmartPLS software to conduct PLS-SEM analysis. Respondents in this study were people in Bandung who had bought cosmetics at Sociolla stores in Bandung, with a total sample size of 261 respondents. The results of research conducted on descriptive analysis have shown that all variables are in the high category. Then, the results showed that price, location, and product diversity had a positive effect on cosmetic purchasing decisions at the Sociolla store in Bandung. Meanwhile, the variables of shop atmosphere and halal awareness have no effect on cosmetic purchasing decisions at the Sociolla store in Bandung. This research implies that the Sociolla store in the city of Bandung can optimize retail marketing strategies through expanding price segmentation, stocking fulfilled goods, and choosing locations with consideration of similar stores, as well as to the government to pay more attention to the spread of non-halal cosmetics.